2013
DOI: 10.1890/es12-00245.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil ingestion, nutrition and the seasonality of anthrax in herbivores of Etosha National Park

Abstract: Abstract. Anthrax, caused by the bacterium Bacillus anthracis, is a seasonally occurring infectious disease affecting primarily herbivorous wildlife and livestock. The seasonality of anthrax outbreaks varies among locations, making it difficult to develop a single consistent ecological description of this disease. Over 44 years of mortality surveillance, most anthrax cases in Etosha National Park, Namibia are observed in the wet season, although elephants have an anthrax mortality peak in the dry season. Focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
138
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(151 citation statements)
references
References 65 publications
13
138
0
Order By: Relevance
“…Previous work in ENP has demonstrated that ungulates ingest significantly more soil in the wet season, likely leading to increased exposure to B. anthracis at that time [27]. In support of this, we found that anti-PA titer prevalence was significantly, positively related to rainfall in the PA GEE ( Figure 3B), likely reflecting this increased exposure to B. anthracis during the wet season, with a subsequent immune response if hosts are exposed to sublethal doses [32].…”
Section: Correlates Of Coinfection With Immunomodulatory Effectssupporting
confidence: 86%
See 2 more Smart Citations
“…Previous work in ENP has demonstrated that ungulates ingest significantly more soil in the wet season, likely leading to increased exposure to B. anthracis at that time [27]. In support of this, we found that anti-PA titer prevalence was significantly, positively related to rainfall in the PA GEE ( Figure 3B), likely reflecting this increased exposure to B. anthracis during the wet season, with a subsequent immune response if hosts are exposed to sublethal doses [32].…”
Section: Correlates Of Coinfection With Immunomodulatory Effectssupporting
confidence: 86%
“…These new helminth infections are constrained to the wet season; the eggs and larvae require for survival moisture and moderate temperatures over the 1-2 week period of development in the external environment before they become infectious to new hosts [23,24]. The wet season is also when ENP plains ungulates experience annual outbreaks of anthrax, a bacterial infection caused by the ingestion of Bacillus anthracis spores from the environment [25,26]; zebra account for 52% of all anthrax cases in ENP, and 57% of all anthrax cases occur in March and April at the middle and end of the rainy season [27]. The reasons for anthrax seasonality, however, are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blowflies have been suspected to play an important role in anthrax transmission in Kruger National Park, South Africa, because of their propensity to ingest material at carcass sites and then regurgitate it on vegetation at heights preferred by the browsing species most frequently infected in that system (36,37). In ENP, however, while we observed similar blowfly feeding preferences (but far fewer flies), the outbreaks occur primarily in grazers and appear more likely to be due to the direct ingestion of contaminated soil (6,20).…”
Section: Discussionmentioning
confidence: 51%
“…The resulting vegetative cells rapidly reproduce in the blood and produce toxins, killing the host within days (3)(4)(5). Along with exposure-related host behavior, species variation in lethal doses, and individual-specific variation in immunity, spore production (i.e., sporulation) and survival play a critical role in anthrax transmission (1,5,6).…”
mentioning
confidence: 99%